TINGKAT PENGETAHUAN TERHADAP PENCEGAHAN COVID - 19 PADA PESERTA PROLANIS DIABETES MELITUS TIPE 2 DI KLINIK IMAN - DESTY ASLYA SARI SINAGA; SHAHRUL RAHMAN (JURNAL ILMIAH MAKSITEK, 2021)
COVID-19 is acute respiratory disease that can attack humans and spreads very easily. COVID-19 can affect everyone, butsomeone who has Diabetes Melitus can have a poor prognosis for the occurrence of COVID-19. The general objective in thisstudy was to determine the level of knowledge on the prevention of COVID-19 in PROLANIS Diabetes Melitus type 2 at theKlinik IMAN. This research is a descriptive study wih cross sectional design, this study uses a total sampling and obtainded asample amount of 38. The level of knowledge of COVID-19 prevention among PROLANIS Diabetes Melitus type 2participants in the category of good knowledge was 18 people (17,4%), 11 people (28,9%) had sufficient knowledge, and 9people (23,7%) had bad knowledge. There was significant relationship between knowledge of COVID-19 prevention inPROLANIS Diabetes Melitus type 2 participants.